Bilateral Sequential Spontaneous Otogenic Pneumocephalus, Lessons in Pathophysiology, and Management of a Rare Case. Issue 10 (December 2020) - Shapiro, Scott B.; Lipschitz, Noga; Tumlin, Parker; Krueger, Bryan; Forbes, Jonathan; Samy, Ravi N.
Abstract : Objective: Report the details of an unusual case of initially unilateral intradural spontaneous otogenic pneumocephalus in which the patient developed contralateral pneumocephalus after surgical repair of temporal bone and dural defects on the initial side. Discuss the lessons learned concerning management and pathophysiology of this rare case. Patient: A 73-year-old male presenting with bilateral retro-orbital pain and headache was found to have unilateral intradural pneumocephalus in the temporal lobe with an adjacent defect in the temporal bone. Intervention: Surgical repair of the initial defect in the temporal bone and dura via a middle cranial fossa approach with obliteration of the mastoid cavity. Results: The patient's symptoms and degree of pneumocephalus on first affected side decreased initially after surgery. Two weeks after surgery he developed worsening pneumocephalus on the contralateral side in the temporal and frontal lobes with weakness and mild somnolence. This side was repaired via a similar technique without mastoid obliteration. Two weeks after surgery the patient recovered to normal level of consciousness with mild residual weakness. Conclusions: Spontaneous otogenic intradural pneumocephalus is an extremely rare but serious condition related to defects in the temporal bone and dura. The precise mechanism by which this occurs is poorly understood. This unusual case where there were bilateral defects presenting with spontaneous otogenic pneumocephalus in sequence illustrates that it represents a rare sequelae of processes which thin the skull base. These processes should be addressed in addition to acute management of the defect and intracranial air.